2016
DOI: 10.1103/physrevd.94.054024
|View full text |Cite
|
Sign up to set email alerts
|

LHCb pentaquarks as a baryon-ψ(2S)bound state: Prediction of isospin-32pentaquarks with hidden charm

Abstract: The pentaquark P + c (4450) recently discovered by LHCb has been interpreted as a bound state of Ψ(2S) and nucleon. The charmonium-nucleon interaction which provides the binding mechanism is given, in the heavy quark limit, in terms of charmonium chromoelectric polarizabilities and densities of the nucleon energy-momentum tensor (EMT). In this work we show in model-independent way, by exploring general properties of the effective interaction, that Ψ(2S) can form bound states with nucleon and ∆. Using the Skyrm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 80 publications
(139 reference statements)
2
70
1
Order By: Relevance
“…where the constant R 0 is determined by the profile function derived by minimizing the classical soliton mass and is given in terms of the axial coupling constant in the chiral limit [31,47].…”
Section: Gravitational Form Factors Of the In The Skyrme Modelmentioning
confidence: 99%
“…where the constant R 0 is determined by the profile function derived by minimizing the classical soliton mass and is given in terms of the axial coupling constant in the chiral limit [31,47].…”
Section: Gravitational Form Factors Of the In The Skyrme Modelmentioning
confidence: 99%
“…After the announcement of the P c (4380) and P c (4450) states by LHCb, these two P c states were interpreted as Σ cD * , Σ * cD , or Σ * cD * molecules [17][18][19][20][21][22][23][24][25][26][27][28], bound states or resonances of charmonium and nucleon [29][30][31][32], diquarkdiquark-antiquark states [33][34][35][36][37][38], diquark-triquark states [39,40], compact pentaquark states [41][42][43], kinematical effects due to χ c1 p rescattering [44], due to triangle singularity [45][46][47], or due to aD-soliton [48], or a bound state of the colored baryon and meson [49]. Their decay and production properties were studied in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In the first place, we recall that those peaks have been interpreted as new resonances given by pentaquark configurations. This interpretation has been developed in the framework of the so-called hadro-quarkonium model, defined more specifically, in this case, as baryo-charmonium model; for an orientation about this model, see references [63][64][65][66][67][68][69][70][71]. But, in this concern, it is necessary to recall that also other theoretical interpretations have been proposed: in Guo et al [72,73], Liu et al [74], and Mikhasenko [75], it has been suggested that these peaks have a non-resonant nature related to the rescattering of known particles, in the triangle diagram, near kinematical thresholds.…”
Section: The Chromo-electric Field Energy In the Context Of Hadronic mentioning
confidence: 99%